Detection of de novo genetic variants in Mayer-Rokitansky-Küster-Hauser syndrome by whole genome sequencing - Hong-xin Pan; Guang-nan Luo; Sheng-qing Wan; Cheng-lu Qin; Jie Tang; Meng Zhang; Min Du; Ke-ke Xu; Jin-qiu Shi (Elsevier, 2019)
Objective: The aim of this study was to use whole genome sequencing (WGS) help detect de novo mutations or pathogenic genes of Mayer-Rokitansky-Küster-Hauser syndrome type 1(MRKH syndrome type 1). Study design: This was a case-parent trios study. Nine unrelated probands, with MRKH syndrome type 1 and their parents were enrolled. The enrollment, sequencing process, establishment of the de novo mutations detecting procedure and experiment part were performed over a 2-year period. Results: we detected 632 de novo single nucleotide variants (SNVs), 267 de novo small insertions/deletions (indels), 39 de novo structural variations (SVs) and 28 de novo copy number alterations (CNAs). Three novel damaging coding de novo SNVs with three damaging coding de novo genes (PIK3CD, SLC4A10 and TNK2) were revealed. Two SNVs were annotated of the promoter region of gene NBPF10 and 3'UTR of NOTCH2NL, potentially contributing to the pathogenesis of MRKH. Conclusion: We identified five de novo mutations in BAZ2B, KLHL18, PIK3CD, SLC4A10 and TNK2 by performing WGS, the functional involvement of all deleterious mutations in MRKH candidate genes of the trios warrant further study. WGS may complement conventional array to capture the complete landscape of the genome in MRKH. Keywords: Next-generation sequencing, Whole-genome sequencing, Mayer-Rokitansky-Küster-Hauser syndrome, De novo mutations